Changes in environmental conditions regulate the biodiversity of planktonic microeukaryotes mediated by the dispersal-selection relationships in river: an example of the Beipan River, Guizhou, China - Dong, Xiaohan; Huang, Jiaxin; Zhou, Xinxin; Ran, Jiali; Wang, Ziwei; Qi, Zongqiang; Shen, Yanjun (Frontiers in Microbiology, 2025)
River planktonic microeukaryotes (phytoplankton and zooplankton) underpin aquatic ecosystem function, yet how environmental change regulates their biodiversity via assembly mechanisms remains poorly understood. Using eDNA metabarcoding along China’s Beipan River, partitioned by a barrier dam into environmentally heterogeneous upstream and stable downstream regions, we assessed plankton diversity and the roles of dispersal and environmental selection. Phytoplankton exhibited higher alpha- and beta-diversity than zooplankton, attributed to stronger dispersal but weaker selection. Conversely, zooplankton showed higher gamma-diversity, likely due to broader niche breadths amplified by environmental heterogeneity. Upstream sites displayed significantly greater alpha-, beta-, and gamma-diversity for both groups, driven by higher environmental heterogeneity. Environmental selection dominated community assembly throughout the river, particularly influencing phytoplankton diversity. Dispersal contributed more to zooplankton gamma-diversity in the homogeneous downstream region. Biodiversity correlated strongly with environmental conditions, especially with COD and TOC levels in the variable upstream zone. Our findings demonstrate that environmental heterogeneity governs plankton biodiversity by regulating the dispersal-selection balance, providing new insights into assembly mechanisms and responses to global change in river ecosystems.